Students' perception toward gamification applied in English language classroom - Putra, Pandu Perdana; Priyatmojo, Arif Suryo (ELT Forum: Journal of English Language Teaching, 2021)
This study aims to find out the students' perception toward gamification applied on English language Classroom. Gamification emerged as an innovation in classroom teaching. The basic concept is to incorporate game elements into teaching, taking advantage of students' interest in games that can be used for the purposes of the teaching process. This study is conducted since there is still limited research that is conducted in Indonesia which analyses the students' perception toward the gamification utilization. This research used qualitative methods as a way to present research results from data collected. Data from this study were collected using two methods, namely online questionnaires, and interviews. This research shared questionnaires to 30 students. The questionnaire was a Likert-style close-ended question. From the research conducted, it was found that the majority of students' perceptions of gamification used in English classes was positive. The students believed that gamification was effective and fun to bring to classroom learning. This teaching method allows students to engage more in-class activities, reduces boredom because it creates a learning atmosphere, and increases learning motivation without disturbing the understanding of the material obtained by students.